Hematopoietic stem cell transplantation: Improving alloreactive Bw4 donor selection by genotyping codon 86 of KIR3DL1/S1. Issue 6 (9th June 2016) - Alicata, Claudia; Pende, Daniela; Meazza, Raffaella; Canevali, Paolo; Loiacono, Fabrizio; Bertaina, Alice; Locatelli, Franco; Nemat‐Gorgani, Neda; Guethlein, Lisbeth A.; Parham, Peter; Moretta, Lorenzo; Moretta, Alessandro; et al.
Abstract : Killer immunoglobulin‐like receptor (KIR) genotyping identifies hematopoietic stem cell donors having NK cells potentially alloreactive toward patient leukemia. KIR3DL1 binds haplotype identical (HLA) molecules expressing the Bw4 ligand, but some KIR3DL1 alleles are not expressed. Donor selection using PCR and sequencing identifies individuals who could become optimum donors for Bw4‐negative patients. Abstract : KIR3DL1 is a natural killer (NK) cell receptor that recognizes the Bw4 epitope of human leukocyte antigen (HLA) class I molecules. Following hematopoietic stem cell transplantation for patients lacking Bw4, KIR3DL1‐expressing NK cells from Bw4‐positive donors can be alloreactive and eliminate tumor cells. However, KIR3DL1 alleles having T instead of C at nucleotide 320 (encoding leucine 86 instead of serine 86) are not expressed on the cell surface. Thus, not all individuals testing positive for KIR3DL1 are optimal donors for Bw4‐negative recipients. Therefore, we developed a method for genotyping codon 86, which was validated by its perfect correlation with NK cell phenotype for 100 donors of diverse KIR3DL1/S1 genotype. We typed 600 donors and found that ∼12.2% had the KIR3DL1 gene, but did not express cell‐surface KIR3DL1. By contrast, high‐expressing allotypes were identified when haplotypes from four families with duplicated KIR3DL1/S1 genes were characterized at high resolution. Identifying donors who have KIR3DL1 but lack cell‐surface KIR3DL1 would refine donor selection. With this technique, the number of individuals identified who may not be optimal donors for Bw4‐negative patients increases by threefold, when compared with standard methods. Taken together, we propose that allele typing of killer cell Ig‐like receptor (KIR) polymorphisms should become a standard practice when selecting donors.